The strange case of Jane O. : a novel - Walker, Karen Thompson (Random House, 2025)
"A woman born with perfect memory suddenly develops a series of eerie psychological symptoms--blackouts, hallucinations, premonitions, an inexplicable sense of dread. It is the first year after her child is born, and she and her untraditional psychiatrist struggle to solve the mystery of what is happening to Jane, to her mind. Then Jane suddenly goes missing and is found a day later lying unconscious in Brooklyn's Prospect Park, with no memory of her missing hours. A police detective becomes suspicious of Jane, and begins to track her, convinced that Jane is lying. What happened to Jane, and what do these peculiar experiences, including in something called a fugue state, have to do with a hallucination Jane has about a young man she knew twenty years ago, who warns her of a disaster ahead? The extraordinary mystery behind Jane's symptoms leads the forward-thinking young Dr. Byrd to reassess everything he thought he knew about Jane, the mind, psychology, and reality, including the events of his own life. This stunning novel is a provocative literary puzzle about memory, identity, consciousness, and the tender bonds of love between people, as well as a celebration of the gymnastic capabilities and the unexplained nature of the human mind"--